An Ideology of Loyalty: Reflections on Herodotus Book III - West, Stephanie (Folia Orientalia, 2026)
The last years of Cambyses’ reign are marked by the extension of Achaemenid rule to Egypt and the prolonged absence of the king and his ministers from the Persian heartlands. Reliable subordinates were obviously essential to the smooth functioning of the Empire, and the role played by Prexaspes, whom Herodotus describes as pre-eminent in loyalty (3.30.3), illustrates what might be required of highly placed officials if the charisma of kingship, the cement that held the Empire together, was to be preserved. Prexaspes’ activity imposes unity on a series of episodes illustrating his unfailing competence in the service of an unbalanced autocrat, and his end brings commendation from Herodotus (3.75.3). An Assyrian counterpart is offered by the story of the wise counsellor Ahiqar, first attested in an Aramaic text from the latter part of the fifth century BC and subsequently translated into a wide range of languages; the tale of Ahiqar’s vicissitudes provides a framework for an assemblage of moral precepts, emphasising loyalty to the sovereign as a religious duty and offering advice to the ambitious. Under Darius self-sacrificing loyalty inspires the extraordinary expedient by which Zopyrus contrives the reduction of the rebellious city of Babylon (3. 150–160). While the narrative of the means by which this was achieved is absurd, it brings out the importance under Darius of incentives to dedicated service, above all the hope of winning recognition from a ruler who could express his appreciation on an extraordinarily generous scale. Merit awards did not depend on whim or haphazard observation; it is significant that Herodotus reports (8.90.4) the presence of scribes recording details of distinguished service at the battle of Salamis. But the list of those termed the King’s benefactors, orosangai (8.85.3), was clearly liberal as to the kinds of activity deemed to qualify for such recognition. To Greeks dedication to the ideology represented by the Persian Empire might seem to entail a distortion of normal values while its rewards appeared rather questionable to those who did not appreciate the advantages of the strong centralized rule which prevented disintegration into lawless tribalism.